Does Immigration Affect Space Identity? Kastamonu Cumhuriyet Square Sample - Belkayali, Nur; Ayan Çeven, Elif (SAGE Publications, 2019)
Humans change places voluntarily or involuntarily because of many factors, such as life struggle, wars, and diseases. The most intense city environments in which these translocations are observed are cities where many native and foreign individuals1 settle with the purposes of job, education, sheltering, and protection. Today, as in many cities of Turkey, it can be observed that the population of neighboring countries’ citizens in Kastamonu is increasing, mostly for educational purposes. The purpose of this study is to determine the effect of cultural differences that especially take place due to migration on the use of public open space. Since squares are the vital points of cities, can be accessed easily by everyone, appeal to everyone, provide opportunity to socializing and they are the democratic environments that symbolize the culture of the city, they were considered to be the public open space which can define the effect of cultural differences in the use of public space the best and in this context Cumhuriyet Square was chosen as the study area which has an important place in the history of the city. In accordance with the aim of the study, the intended use of the square by foreign individuals from different cultures was determined, and therefore, it was aimed to reveal in what way the square was affected by this movement of migration. In the scope of the study, observations were made with area studies, and also 170 questionnaire studies were conducted with the users of the area. As a result of the study, a statistically significant difference was determined between the intended use of the Cumhuriyet Square, which has an important value for the identity of the city, by the local people and foreign individuals. It is required for foreign individuals to socialize with the local people in relation to adopting the space by improving their sense of belonging to prevent the identity of the space to be affected negatively and to create a common value on the emergence of a common culture, and it is considered that the most appropriate place for these values to emerge is squares which are one of the public open spaces.
Keywords: H; AZ20-999; Social Sciences; History of scholarship and learning. The humanities; 11. Sustainability; 16. Peace & justice